(untitled) (Revista Contexto & Educação, 2025)
The Expanded Family Health and Primary Care Center (NASF-AB) advocates the implementation of intersectoral articulations, with health education activities being one of the fundamental axes of the speech-language-hearing performance with education professionals. In this context, the present study aimed to describe the production of health education activities developed by speech-language-hearing therapists from NASF-AB for education professionals in the geographic regions of Brazil, from 2016 to 2022. This is an ecological study based on data from the Health Information System for Primary Care. Records of health education activities, both general and specific to education professionals, were considered, in addition to the number of participants reached. Descriptive analysis was used to interpret the data. The results indicated that, throughout the period analyzed, the Northeast and Southeast regions concentrated most of the activities carried out and participants. The proportion of actions aimed specifically at education professionals was more significant in the South region and restricted in the Central-West region. In general, the production of these activities showed growth until 2019, followed by a sharp reduction in 2020. The panorama presented suggests that educational practices aimed at education professionals are still incipient and present regional discrepancies in Brazil. To strengthen the partnership between speech-language-hearing therapists and education professionals, as well as to improve health education strategies, future research is essential.